Structure and composition of trees and their effect on crop yield in existing agrihortisilvicultural and agrihorticultural systems of Garhwal Himalaya - Bijalwan, Arvind; Sharma, C.M.; Sah, V.K.; Raj, A.J. (Indian Journal of Agroforestry, 2020)
The paper summarizes with structure and composition of tree species and productivity of agricultural crop under existing agroforestry systems viz. agrihortisilviculture (AHS) and agrihorticulture (AH) systems in mid hill situation of Garhwal Himalaya between 1000 to 2000m asl during Rabi and Kharif seasons in the year 2004-2006. The northern aspect was more diverse and formed good vegetation composition. In the northern aspect 21 tree species were recorded in AHS system compared to 13 in southern, whereas in AH system the reported tree species were 11 and 9 in northern and southern aspects respectively. In the northern aspect of AHS system, Quercus leucotrichophora was observed as dominant tree species followed by Celtis australis and Grewia optiva while in southern aspect Grewia optiva was reported as dominant species. In AH system Malus domestica (apple) and Prunus armeniaca (wild apricot) were dominant fruit trees in northern and southern aspect respectively. In the agricultural crop (Rabi + Kharif) the grain yield was recorded highest 1197 kg/ha/yr and biological yield 4110 kg/ha/yr under AHS in northern aspect as compared to 2027 and 6070 kg/ha/yr in sole cropping. Overall there is an average reduction of 46.38 percent in gain yield and 39.93 percent in biological yield compared to sole agricultural cropping but this reduction is supplemented by multipurpose benefits of wood production which is supporting life of the rural community of this hilly region.